Republic of South Sudan : Staff-Monitored Program and Request for Disbursement under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Republic of South Sudan. (IMF Staff Country Reports; Country Report ;, 2021)
South Sudan is a very fragile post-conflict country. After five years of civil conflict, the warring parties came to an agreement for power-sharing in September 2018 and formed a unity government in February 2020. However, peace remains fragile in the face of difficult humanitarian and economic conditions. Already very high levels of poverty and food insecurity have been exacerbated by severe flooding in recent months. The floods (the worst in 60 years) have killed livestock, destroyed food stocks, and damaged crops ahead of the main harvest season. South Sudan's economy has been hit hard by lower international oil prices following the COVID-19 pandemic.